PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BNI LIFE INDONESIA JAKARTA SELATAN - Firmansyah; Tjeri Hadjirillah (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the effect of work stress and work environment on employee performance at PT BNI LIFE INDONESIA JAKARTA SELATAN. The method used in this research is a quantitative method with the research object being employees of PT BNI LIFE INDONESIA. The sample consists of 50 employees, selected using purposive sampling technique. Data were collected through questionnaires distributed to respondents. Data analysis was performed using the Statistical Package for the Social Science (SPSS) Version 26, which includes validity tests, reliability tests, classical assumption tests, as well as simple and multiple linear regression analysis. The results of the study indicate that work stress has a positive partial effect on employee performance, with a t count of 6.008 which is greater than the t table of 2.001 and a significance value of 0.000. Additionally, the work environment also has a positive effect on employee performance, with a t count of 4.806 which is greater than the t table of 2.001 and a significance value of 0.000. Simultaneously, work stress and work environment have a positive and significant effect on employee performance, with an F count of 24.923 which is greater than the F table of 3.16 and a significance value of 0.000. From this study, it can be explained from the T Test that Work Stress (X1) is 7.155 and the Work Environment (X2) is 3.789 so that Work Stress has the most influence on Employee Performance (Y). and obtained from the results of the F Test, namely if the ftabel = 3.191 is obtained. because fcount> ftabel23,191> 25.573and the significant value is 0.000 <0.05 so that it can be concluded that the independent variables, namely work stress (X1) and work environment (X2) together (simultaneously) have a significant effect on employee performance variables (Y).